2018
DOI: 10.5603/gp.a2018.0104
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor therapy for endometrial stromal sarcoma — two-centre experience

Abstract: Objectives: Endocrine therapy is the recommended systemic treatment for steroid receptor positive endometrial stromal sarcoma (ESS). There is no current consensus on the optimal hormonal therapy for ESS. The literature offers several reports on advanced/recurrent/metastatic ESS patients treated with progestins, whereas data on the efficacy of aromatase inhibitors are scarce. Material and methods: We retrospectively identified cases treated for ESS with aromatase inhibitors at our institutions. There were five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…However, efficacy of progestins such as megesterol acetate, and aromatase inhibitors (AI) have been demonstrated for patients with unresectable advanced disease [6,7]. Owing to its rarity, the data showing objective responses with these agents are derived from case reports and small series, mainly with megesterol acetate and letrozole [8]. Serkies et al, in their retrospective study, identified only 5 cases treated with aromatase inhibitors from two institutions over a 10-year period, which highlights the rarity of this disease [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, efficacy of progestins such as megesterol acetate, and aromatase inhibitors (AI) have been demonstrated for patients with unresectable advanced disease [6,7]. Owing to its rarity, the data showing objective responses with these agents are derived from case reports and small series, mainly with megesterol acetate and letrozole [8]. Serkies et al, in their retrospective study, identified only 5 cases treated with aromatase inhibitors from two institutions over a 10-year period, which highlights the rarity of this disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not clear if lung metastasis is associated with a more aggressive course or with durable responses to aromatase inhibitors. In the reported literature we identified a few cases with lung metastasis treated with letrozole (Table 1) [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…National Comprehensive Cancer Network (NCCN) and ESMO guidelines recommend adjuvant CT for high risk patients with uterine sarcoma (6) . Hormonal therapy have been suggested to be efficacious in the treatment of ESS, but there is a lack of data regarding the optimal usage (26) . According to the guideline of DGGG and OEGGG, adjuvant CT should not be generally administered and it should depend on the presence of other risk factors (15) .…”
Section: Tab 4 the Treatment Modality And Recurrence Pattern Of Patmentioning
confidence: 99%
“…According to the guideline of DGGG and OEGGG, adjuvant CT should not be generally administered and it should depend on the presence of other risk factors (15) . It is also remarkable that the molecular patterns of these tumors are totally different (26,27) . In a large retrospective series including 419 patients with uterine sarcomas, the stage of disease was reported as the most important prognostic factor for all tumor types.…”
Section: Tab 4 the Treatment Modality And Recurrence Pattern Of Patmentioning
confidence: 99%